Elevated Glycated Hemoglobin Levels Are Associated With Poor Outcome in Acute Ischemic Stroke - Dong, Nan; Shen, Xiaozhu; Wu, Xuan; Guo, Xianghong; Fang, Qi (Frontiers in Aging Neuroscience, 2022)
Objective: Admission hyperglycemia is an established risk factor for functional outcome in patients with acute ischemic stroke. However, the association between glycated hemoglobin (HbA1c) and prognosis in patients with acute anterior circulation ischemic stroke (AACIS) remains controversial. This study aimed to explore whether elevated HbA1c levels are associated with functional outcome in AACIS patients. Participants and Methods: We enrolled patients with AACIS hospitalized in the First Hospital Affiliated to Soochow University from March 2018 to January 2021. Patients were categorized into three groups based on baseline HbA1c: HbA1c ≤6.5%, 6.5%< HbA1c ≤8.0%, and HbA1c >8.0%. Ninety-day modified Rankin Scale scores of 0–1 and 0–2 were defined as excellent and favorable functional outcome, respectively. Early neurological improvement was regarded as a reduction in the National Institutes of Health Stroke Scale (NIHSS) score ≥4 points compared with that on admission, or an NIHSS score of 0–1 at discharge. The association between HbA1c and clinical outcome in acute ischemic patients was assessed by logistic regression and adjusted for confounding factors. Subgroup analyses by TOAST classification were also conducted. Results: The study included 326 patients. The proportion with favorable outcome was significantly lower in the HbA1c >8.0% group than the HbA1c ≤6.5% group (30.4% versus 55.2%; p<0.01). Binary logistic regression analysis demonstrated that increasing HbA1c levels (as a continuous variable) were associated with reduced functional independence (adjusted OR=0.739; 95% CI: 0.605–0.904; p=0.003). In subgroup analyses, higher HbA1c was also associated with favorable outcome in large-artery atherosclerosis (LAA)-type patients (adjusted OR=0.776; 95% CI: 0.614–0.981; p=0.034), but not in LAA group. Conclusions: HbA1c level was an independent predictor of worse functional outcome in patients with AACIS, particularly in those with LAA. For patients with anterior circulation atherosclerosis, strict adherence to a target HbA1c <6.5% may be required.